Communication Patterns of Minang Students in Yogyakarta in Maintaining Good Relationships with Parents - David Dwi Pangga; Suciati (Jogjakarta Communication Conference (JCC), 2026)
Digital communication within migrant student families plays a crucial role in maintaining the continuity of relationships between children and their parents. This study aims to describe the communication patterns of Minangkabau students who migrate to Yogyakarta in sustaining their relationships with their parents. The research employs a descriptive qualitative approach. Data were collected through in-depth interviews. A purposive sampling technique was used to select informants aligned with the research objectives: Minangkabau students who had migrated for at least 6 months and regularly communicated with their parents via digital media. Data validity was ensured through source triangulation and prolonged engagement. The findings indicate that the coordinative pattern emerged as the most dominant pattern across the three informant pairs. This pattern is characterized by communication triggered by financial and academic administrative needs, accompanied by rational explanations, clarification, negotiation, and parental validation before decisions are made. Educational demands shape the coordinative pattern, students’ financial dependence, Minangkabau cultural values embedded in the tradition of merantau, an interdependent family relational structure, and the support of digital communication technologies. These findings demonstrate that family communication in the context of educational migration not only maintains emotional closeness but also serves as a mechanism for shared decision making.